Case Report: Damaged external limb of montgomery T-tube in a child: a rare complication - Wang, Ting; Wu, Wenjie; Chen, Xing; Liu, Ling; Yin, Huaxu; Xue, Bing; Zhang, Jie (Frontiers in Pediatrics, 2025)
Montgomery T-tubes (MT) are well tolerated with rare complications. Here, we report an unusual complication of damaged external limb of the MT in a child. Both physicians and patients should be aware of this possible complication, which can lead to potential fracture of the MT, resulting in unusual airway problems requiring emergency management.